Relationship between foot angles and hypermobility scores and assessment of foot types in hypermobile individuals - Kamanli, A; Sahin, S; Ozgocmen, S; Kavuncu, V; Ardicoglu, O (Sage Publications Inc, 2004)
This study proposed to assess foot types and radiological examination of feet of individuals with hypermobility syndrome in comparison to healthy matched controls for age, sex, and body mass index. The relationship between foot angles and hypermobility scores of subjects in both groups were also assessed. Twenty individuals having joint hypermobility syndrome previously diagnosed according to Beighton and Bulbena scores were compared to 20 healthy subjects. Standing anteroposterior (AP) and lateral weigthbearing radiographs of feet of the individuals were taken. Foot angles and foot types were evaluated on the AP and lateral views. The mean +/-SD of Beighton and Bulbena scores were significantly higher in the hypermobile individuals (p <.001) than in controls. In both groups, Egyptian and square types of feet were mostly encountered (p >.05). Bilateral calcaneal pitch (CP) angles (p <.001), bilateral talometatarsal (TM) angles (p <.01), and right apex angles (p <.05) were significantly low in hypermobile individuals, whereas first metatarsophalangeal (MTP) angles were significantly high (right foot, p <.01; left foot, p <.05) as compared to the control group. Hypermobility scores correlated negatively with bilateral CP and TM angles and positively with bilateral first MTP angles. No correlation was found for the other angles. These finding suggest that foot angles (especially CP, TM and first MTP angles) are in relation with severity of hypermobility. There was no difference between foot types in the hypermobile individuals and healthy controls. These angles may be useful for clinically monitoring the foot health in the hypermobile individuals.
Keywords: Beighton; Bulbena; foot radiograph; foot types; hypermobility